Scaffolding the Development of English Language and Communication Skills of Engineering Students - Azwani Mohamed, Mimi Nahariah; Mohd Muji, Siti Zarina; Jamari, Suzilla; Ahmad Powzi, Nor Fadhilah; Abd Samad, Nurzarina; Othman, Nurul Ain (Horizon Research Publishing Corporation, 2020)
Teaching English in higher institutions is becoming more challenging in this globalised era. With the demand for communication skills in English as one of the important recruitment criteria, future graduates need to be equipped with sufficient English language and communication abilities relevant for their respective fields. This suggests that English language educators need to teach specialised English language such as engineering which may be beyond their expertise. Having trained as English as a second language educators, most of them may have limited knowledge in engineering. This paper is part of a larger research that explores the development of cross-disciplinary curriculum. This study examined the extent to which English language educators addressed the language needs of engineering students academically and professionally. A total of ten language educators from two Malaysian public universities participated in a focus group where they discussed their teaching practices and experiences in teaching engineering students. In addition, six English for Specific Purposes (ESP) practitioners from European universities were also interviewed to obtain information regarding the practices in teaching ESP at their universities. The results show that there is a gap between the development of engineering students' English language abilities in English language classrooms and its maintenance in engineering classrooms in Malaysia. The study highlights the key considerations to develop a framework that scaffolds the development of English language abilities and communication skills among engineering students within engineering education.